Defective Tool Embodiment in Body Representation of Individuals Affected by Parkinson’s Disease: A Preliminary Study - Scarpina, Federica; Cau, Nicola; Cimolin, Veronica; Galli, Manuela; Priano, Lorenzo; Mauro, Alessandro (Frontiers in Psychology, 2019)
When efficiently used for action, tool becomes part of body, with effect on the spatial temporal movement parameters and body size perception. Until now, no previous investigation was reported about tool embodiment in Parkinson’s disease (PD), that is a neurological disease characterized by several sensory and motor symptoms affecting body and action. We enrolled fourteen individuals affected by PD and eighteen healthy individuals as controls. We studied the spatial-temporal parameters on self-paced free pointing movements task, via an optoelectronic system, before and after a short training in which a 27 cm long rod was used to point toward a far target. Moreover, we investigated changes in estimation of arm length through the Tactile Estimation Task. After the tool use training, controls showed changes in spatial-temporal parameters: they were slower to perform movements and reported higher value of deceleration, respect to the baseline. However, such a difference did not emerged in the PD individuals. In the Tactile Discrimination Task, no difference emerged before and after the tool use training in both groups. Our results were suggestive of possible difficulties of tool embodiment process in PD. We discussed our results in relation to aberrant multisensory integration as well as in terms of the effect of PD sensory and motor symptoms on body schema plasticity. The present study points at a novel way to conceive PD sensory motor signs and symptoms, in terms of their effect on individuals’ body representation.